Relationship between cognitive performance, academic performance, and sleep quality with bedtime mobile phone use among undergraduate students in a public university in Malaysia - Ragupathi, Darnisha Devi (2020)
In the present time, technology plays a huge role in every individual’s life with an immense increase in its usage that enables an individual to access almost anything and everything at their fingertips. A form of addiction has been seen and mobile phone use accounts to the highest form of technology usage among the other available technology devices. Young adults are the majority group of individuals who are actively seen to be involved in excessive usage of mobile phone specifically during nocturnal hours in their bedroom. This has caused a huge burden to young adult’s life in relation to their cognitive performance, academic performance, and sleep quality. The purpose of this research is to examine the relationship between cognitive performance, academic performance, and sleep quality with bedtime mobile phone use. This study was conducted among 385 undergraduate students at Universiti Putra Malaysia, Serdang based on a multistage design that involved stratification and random number sampling procedure. The two strata were Year 1 and Year 2 of study. The faculties, courses, and number of undergraduate students were chosen based on random number selection procedure with regards to the listed criteria. Data was collected using computerized test as well as paper and pencil test. Pearson’s correlation was used to analyse the relationship between the variables and hierarchical multiple linear regression was used to identify the significant contributors to bedtime mobile phone use. Statistical Package for Social Science (SPSS)® Version 25 was used to perform statistical analysis. Respondents had an overall good cognitive performance and academic performance. However, out of 385 respondents, 328 (85.2%) respondents had poor sleep quality. Findings of this study showed that out of 385 respondents, 211 (54.8%) respondents had high frequency of bedtime mobile phone use. The results obtained has disclosed that only academic performance and sleep quality was significantly correlated with bedtime mobile phone use. The hierarchical multiple regression analysis showed that academic performance and sleep quality were the significant predictors of bedtime mobile phone use. Poor academic performance and poor sleep quality collectively predicted higher frequency of bedtime mobile phone use. Cognitive performance did not predict bedtime mobile phone use. This study provides evidence to young adults of their rate of dependence on mobile phone specifically at night. It brings them awareness of the importance of positive sleep habits that could reduce their dependence on mobile phone at night. Besides that, this study provides preventive measures and early identification of the problematic behaviour as such as poor academic planning that is characterised in an increase in their need to use mobile phone during bedtime for study purposes. This study highlights the role of young adults, public health authorities and policy makers, school community, parents, and device technologist to target issues and negative impacts of undesirable bedtime mobile phone use.